Comparing pharmacy practice in health facilities with and without pharmaceutically trained dispensers: a post intervention study in Tanzania - Romuald Mbwasi; Kelvin Msovela; Fiona Chilunda; Sia Tesha; Robert Canavan; Karin Wiedenmayer (Taylor & Francis Group, 2024)
ABSTRACTBackground: The critical shortage of comprehensively trained healthcare staff in Tanzania affects the capacity to deliver essential health services, attain universal health coverage and compromises health outcomes. There is a specific lack of suitably trained pharmaceutical professionals, thus, an increase in the use of unqualified or poorly trained staff. Following the introduction of a one-year pharmacy dispenser course intervention, this study explored the impact that the new cadre of graduates had on pharmacy practice compared to healthcare facilities with non-pharmacy trained dispensers (NPTDs).Methods: A post intervention assessment was conducted in 2021 using questionnaires formulated to measure indicators of Good Pharmacy Practice, comparing 29 public health facilities employing pharmacy-trained dispensers (PTD) with 32 public health facilities with NPTDs in Dodoma, Shinyanga and Morogoro regions of Tanzania. Data were collected by experienced pharmacists or pharmaceutical technicians and subsequently aggregated and statistically analysed.Results: The dispensing times for medicines were found to be the same for PTDs and the NPTDs (2 min). There were no statistically significant differences in the adequacy of labelling elements between PTDs and NPTDs. Patients' level of knowledge of the medicines dispensed to them, from both PTDs and NPTDs, showed no difference. Moreover, no differences were observed in storage practice and documentation performance, records of dispensed medicines, handling of medicines and the dispensing area cleanliness between both groups. Overall, facilities with PTDs averaged a higher availability of tracer medicines (77%) than those with NPTDs (70%), however, availability of health commodities in all health facilities in the three regions was low and there was no statistically significant difference between both groups.Conclusion: The study showed no significant difference in performance of pharmacy practice between PTDs and NPTDs despite the former undertaking a one-year training course intended to improve knowledge and skills. Practice application not only depends on effective training but on the working environment. Clear job descriptions, appropriate tools and references to guide, Standard Operating Procedures, acceptance by management of the training undertaken to actively encourage recruits to apply these new skills could improve PTDs performance. Training and knowledge alone do not seem to lead to better practice and performance.